Impact of vagus nerve cross-sectional area on electrocardiogram parameters in community-dwelling older adults: The YAHABA study - Nao Onodera; Kazumasa Oura; Hiroshi Akasaka; Naoki Ishizuka; Tohru Fujiwara; Ryo Itabashi; Tetsuya Maeda (PLoS ONE, 2026)
Objectives The aim of this study was to investigate the association between vagus nerve cross-sectional area (VN-CSA) using carotid ultrasonography and electrocardiogram (ECG) parameters in community-dwelling older adults, thereby clarifying the influence of VN-CSA on cardiac electrical activity. Methods A cross-sectional study examining the association between VN-CSA and ECG parameters. We prospectively enrolled participants aged ≥65 years who underwent both 12-lead ECG and carotid ultrasonography from the 2023 survey of a community-based cohort study (YAHABA study). The VN-CSA was measured offline at the thyroid level using carotid ultrasonography with a 3–8 MHz linear probe. Participants were divided into tertiles of each side; right tertile (RT)1 (<1.0 mm), RT2 (1.0–1.1 mm), and RT3 (>1.1 mm 2 ). and left tertile (LT)1 (<0.9 mm 2 ), LT2 (0.9–1.0 mm 2 ), and LT3 (>1.0 mm 2 ). ECG parameters were compared among the three groups on each of the left and right sides. Furthermore, linear regression analysis was performed to examine the association between left and right VN-CSA and ECG parameters. Results Finally, 183 participants enrolled in this study. In the analysis of covariance in multiple comparisons among tertiles of each side, RT1 had a higher heart rate (p = 0.021), a shorter R–R interval (p = 0.037), and a higher P-wave amplitude (p = 0.008) than RT2, while no significant differences were observed between RT1 and RT3. No significant associations were observed for the left VN-CSA. In the linear regression analyses, significant associations were observed between the left VN-CSA and QRS duration (p = 0.038), while there was no significant association between the right VN-CSA and ECG parameters. Conclusion The size of the vagus nerves had different effects on cardiac electrical activity in the left and right sides. The right VN-CSA may be associated with the electrical activity of the sinus node and atria, while the left VN-CSA may be associated with the electrical activity of the ventricles.